KONSTRUKSI REALITAS MAKNA “ BAJAPUIK” PADA PERNIKAHAN BAGI PEREMPUAN PARIAMAN DI KECAMATAN PASIR PENYU - Bunga Moeleca; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tradition bajapuik (japuik, shuttle) is a tradition that marriage is a trade mark of Pariaman area. Tradition bajapuik seen as the duty of the woman's family gave a number of items or money to men (future husband) before the ceremony performed. This study raises a bajapuik tradition which has grown in the district Sand Turtle. This study aims to determine the motive, knowledge and experience as well as the values contained in bajapuik tradition.This study used a qualitative method with phenomenological approach Schutz. The subjects were 10 women in sub pariaman turtle sand and selected by the snowball technique. To get the data, the authors used three data collection techniques, ie observation, in-depth interviews, and documentation. This study uses data analysis techniques phenomenological research according to Creswell, using the techniques of observation perseverance, the extension of participation, and the adequacy of reference.Results showed that women have a motive pariaman motivated by motives "because" (past) that women wear traditional pariaman bajapuik in marriage is because it has been the tradition and customs of their native areas and still run if married to fellow Pariaman too, and follow the way provisions of the Prophet Muhammad. The second motive "for" (the present) that is to maintain the tradition that has existed since the first as well as to appreciate the male origin in order not to underestimate Pariaman and humbled. Knowledge about the procession of women pariaman custom bajapuik based on their experience that is unique tradition, but takes a lot of time. If you do not use this custom to get a waffle from the person (fellow pariaman). as well as the values contained in this tradition is the value of religion because in accordance with the provisions of the Prophet Muhammad, the unique cultural values as well as transaction marriage and social values, so that the man (husband) is no authority in the family home (female) later. So the starting point of the indigenous traditions that exist in the district bajapuik turtle sand that is like saying "who ducked anyone hunchback, who jumped who broke"KATA KUNCI : MOTIF, PENGETAHUAN DAN PENGALAMAN, NILAI-NILAI, KONSTRUKSI MAKNA BAJAPUIK., FENOMENOLOGI.